2018
DOI: 10.3389/fbioe.2018.00036
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Axis Expression in Dental Pulp Cells Derived From Carious Teeth

Abstract: The insulin-like growth factor (IGF) axis plays an important role in dental tissue regeneration and most components of this axis are expressed in human dental pulp cells (DPCs). In our previous study, we analyzed IGF axis gene expression in DPCs and demonstrated a novel role of IGF binding protein (IGFBP)-2 and -3 in coordinating mineralized matrix formation in differentiating DPCs. A more recent study from our laboratory partially characterized dental pulp stem cells from teeth with superficial caries (cDPCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…The previous studies regarding BMSCs also showed that IGF1 promoted osteodifferentiation of BMSCs and could even be regarded as an alternative biomarker to bone morphogenetic protein-7 [ 54 , 55 ]. In addition, the IGF axis (e.g., IGF-2 and IGFBP-2) was activated under osteogenic conditions in DPSCs, indicating its promoting role in DPSC osteodifferentiation [ 56 ]. THBS1 (thrombospondin-1) is a major regulator of latent TGF- β activation [ 57 ], which can inhibit osteoblast differentiation in BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies regarding BMSCs also showed that IGF1 promoted osteodifferentiation of BMSCs and could even be regarded as an alternative biomarker to bone morphogenetic protein-7 [ 54 , 55 ]. In addition, the IGF axis (e.g., IGF-2 and IGFBP-2) was activated under osteogenic conditions in DPSCs, indicating its promoting role in DPSC osteodifferentiation [ 56 ]. THBS1 (thrombospondin-1) is a major regulator of latent TGF- β activation [ 57 ], which can inhibit osteoblast differentiation in BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Masuda et al showed that laser irradiation of rat incisors enhances GHR and IGFBP5 expression in addition to other genes related to odontoblast-differentiation and formation [ 99 ]. In 2018, Alkharobi’s group also demonstrated a novel role of IGFBP2 and IGFBP3 in cell response to mild inflammatory environment associated with superficial caries by showing that DPCs from teeth with superficial caries display higher levels of IGFBP2 and IGFBP3 when compared to cells isolated from healthy teeth [ 100 ].…”
Section: Gh/igf and Oral Tissue Engineeringmentioning
confidence: 99%
“…Secretome analysis of cells encapsulated within NapFF ε K ε K-OH hydrogels suggested that out of five bioactive factors (VEGF, fibroblast growth factor (FGF), epidermal growth factor (EGF), platelet-derived growth factor (PDGF) and insulin-like growth factor (IGF)) commonly utilised in tissue engineering [ 52 ], all but IGF were shown to increase in NapFF ε K ε K-OH hydrogel versus 2D culture. Interestingly, within the dental pulp IGF is associated with osteo/odontogenic differentiation [ 53 , 54 ] and levels may not therefore be expected to be so closely linked with angiogenesis or vascularisation.…”
Section: Discussionmentioning
confidence: 99%